DISSEMINATED NON SMALL-CELL LUNG CANCER: POSSIBILITIES OF DRUG THERAPY IN THE FIRST DECADE OF THE XXI CENTURY - A. M. Garin (Klinicist, 2014)
In the review the data on the incidence of lung cancer in Russia and the world is presented. Effectiveness of different screening methods used to identify patients with lung cancer, the value of different diagnostic methods is discussed. The data on the current drug therapy of non small-cell lung cancer , built on the basis of doublets of cisplatin and carboplatin used in the first line therapy, as well as on the doublets without cisplatin or carboplatin, generally used in the second line therapy and target therapies which are prescribed separately or in combination with chemotherapy. Indicated the efficiency of certain chemotherapy regimens, data on one-year, sometimes two-year survival, median survival, the major toxicity of combinations, doses, drugs and detailed diagrams of their prescription.